A one-dimensional biomorphodynamic model of tidal flats: Sediment sorting, marsh distribution, and carbon accumulation under sea level rise. (July 2016) - Zhou, Zeng; Ye, Qinghua; Coco, Giovanni
Highlights: A biomorphodynamic model coupling two-way biophysical interactions is developed. Vegetated and bare tidal flats respond differently to wave action. Sea level rise (SLR) drives landward migration of salt marshes and mud zone. Differential deposition results in steeper marsh-edge transition zone. Carbon accumulation on marshlands may be enhanced with an increasing SLR rate. Abstract: We develop a biomorphodynamic model to investigate sediment and vegetation dynamics on a schematic intertidal flat characterized by an initially well-mixed sand-mud mixture. Major interactions between tides, wind waves, salt marshes, sediment transport and sea level rise (SLR) are taken into account. For a bare flat under only tidal action, the model predicts a convex cross-shore profile with the surficial distribution of mud and sand on the upper and lower part of the intertidal flat, respectively. When wind waves are strong, the intertidal flat is highly eroded resulting in a concave profile near the high water mark. This behavior is pronouncedly altered when the intertidal flat is vegetated with the presence of salt marshes. Numerical results suggest that a considerable amount of mud can still remain in the vegetated region even when wave action is strong. A steeper transition zone forms at the boundary between salt marshes and bare flats because of the differential sediment deposition in the two neighboring regions. The inclusion of wind waves is found to considerably enhance the size of the marsh-edge transition zone. For the numerical experiments designed in this study, the profile shape and sediment sorting behavior of tidal flats are not significantly modified by a gradual rising sea level. However, the impacts of SLR on vegetated tidal flats are still manifold: (a) driving the landward migration of intertidal zone and salt marshes; (b) enhancing sediment erosion on intertidal flats; and (c) drowning salt marshes under limited sediment supply with the constrain of seawalls. Finally, model results suggest that organic carbon accumulation on marshlands may be enhanced with an increasing SLR rate provided that salt marshes are not drowned.